Efeito da prática de curta duração no alcance manual de lactentes pré-termo tardios: ensaio clínico controlado randomizado - Soares, Daniele de Almeida (Universidade Federal de São Carlos, 2014)
Objective: This thesis investigated the effect of a few minutes of reaching practice under different practice schedules on the reaching behavior of late preterm infants at the onset of goal-directed reaching. Method: This is a blind, three-arm parallel-group, randomized controlled trial. Thirty six late preterm infants (16,7 ± 2,3 weeks, chronological age) were allocated into groups that received reaching practice based on either a blocked schedule, a serial schedule, or no practice. The infants were assessed 3.3 ± 1.4 days after the onset of goal-directed reaching in three tests: pre-test (immediately before practice), post-test (immediately after practice), and retention test (24 h after post-test). Practice was applied between the pre- and the post-test (intrasession) and consisted of a 4 min. session of induced reaching using a toy in three activities guided by a physical therapist. The activities were elicited in separate blocks for the blocked practice group and in a serial order for the serial practice group. The control group stayed in the physical therapist s lap and was not stimulated to reach. During assessments, the infants were seated in a baby chair reclined 45º from the horizontal axis. A toy was presented at his/her midline within reaching distance for 2 min. The assessments were filmed and the images analyzed considering the following variables: number of reaches, proportions of proximal adjustments (uni and bimanual), distal adjustments (hand opening) and grasping outcome (reaches with and without grasping), and kinematic variables (straightness index, deceleration index, movement units, and velocity). Results: The major findings were increased amount of reaches from pre- to post-test for the serial practice group (p < 0.01). At the pre-test, the serial practice group performed unimanual reaches only; at the post-test, those infants increased the proportion of bimanual reaches compared to the pre-test (p = 0.05). There were no diferences between groups. Conclusions: Serial practice schedule may have required less perceptive and motor demands from the late preterm infants. The toyoriented experience, which stimulated the infants to perceive and act upon the toy successfully in a serial practice schedule, may have favored the infants perceptionaction coupling. This may have provided them with new oportunities to explore strategies to potentialize the transport of the hand towards the toy. Such stimuli were enough to lead to immediate, temporary adaptative changes.
Keywords: Prematuros; Desenvolvimento infantil; Intervenção precoce; Premature; Child development; Early intervention; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL